2006
DOI: 10.1039/b510963a
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of homogeneous nucleation of nanosized zeolite A

Abstract: The formation of zeolite A (LTA) in the presence of tetramethylammonium cations is studied using in situ small angle and wide angle X-ray scattering (SAXS/WAXS) techniques. The SAXS measurements show the formation of homogeneous precursors 10 nm in size prior to the crystallization of LTA which were consumed during the crystallization. The crystal size is estimated by fitting the SAXS patterns with an equation for a cubic particle, and it is revealed that the final crystal size of the LTA depends on the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…4 shows a clearer view of the scattering profile changes of the first two frames (log I(q) versus log q), before the onset of crystallisation. Unlike the report on zeolite A synthesis by Sankar et al, no marked features associated with the presence of clear primary units are visible in the SAXS scattering profile [15,19].…”
Section: Particles Size and The Guinier Regioncontrasting
confidence: 76%
See 1 more Smart Citation
“…4 shows a clearer view of the scattering profile changes of the first two frames (log I(q) versus log q), before the onset of crystallisation. Unlike the report on zeolite A synthesis by Sankar et al, no marked features associated with the presence of clear primary units are visible in the SAXS scattering profile [15,19].…”
Section: Particles Size and The Guinier Regioncontrasting
confidence: 76%
“…Many research groups have shown that SAXS can be successfully employed to follow the crystallisation of ordered micro and mesoporous structures [14][15][16][17][18][19]. SAXS is a non-destructive method, does not require special sample preparation and permits the in situ reaction analysis.…”
Section: Introductionmentioning
confidence: 99%
“…3 ) are predominantly comprised of soluble monomers and/or small oligomers. Prior studies have shown that (alumino)silicate particles or sol gels in LTA growth solutions are sites for heterogeneous nucleation 24 , while homogeneous nucleation has been observed in solutions devoid of amorphous precursors 30 . The clear solutions used in this study differ from those of other zeolites, such as silicalite-1, which are predominantly suspensions of nanoparticles (1–6 nm) 31 – 33 that attach to crystal surfaces and undergo structural rearrangement to incorporate into the underlying crystal lattice 9 .…”
Section: Resultsmentioning
confidence: 99%
“…During the early stages of zeolite synthesis, growth mixtures containing numerous amorphous precursors lead to crystallization by particle attachment, or CPA (4,22,25,26). As the synthesis nears completion, the consumption of precursors results in growth solutions containing mostly monomers where the predominant mode shifts to a classical mechanism; however, recent studies have shown that the use of organics as either structuredirecting agents (SDAs) (27)(28)(29) or zeolite growth modifiers (24,30) can selectively switch the mode of growth between CPA and monomer addition.…”
mentioning
confidence: 99%